N-based s-block complexes: synthesis and application in catalysis - Ried, Alexander C. A. (2018)
The history of organomagnesium chemistry spans over a century of research and discovery, during which alkaline earth coordination compounds and organometallics have seen more than one renaissance. They have proven valuable synthetic tools, widened our fundamental understanding of inorganic chemistry, and been applied to a growing number of catalytic transformations. Due to s-block bonding behaviour, advances in the latter two areas heavily draw on the stabilisation afforded by sterically demanding ligand systems, commonly featuring N-based donor sites. It is the development of such tailored supportive frameworks that has enabled the isolation and study of remarkable s-block species. Reported herein is the exploration of the s-block chemistry of aminopyridinide and pyridylpyrrolide systems, as well as the conceptualisation of novel benzylanilide and tritylamide frameworks and their utilisation in the same. Employing external donor entities enabled the isolation of the first heteroleptic alkaline earth halide supported by the above aminopyridinide system (4). An analogous pyridylpyrrolide complex (11) was synthesised, and the s-block chemistry of such frameworks considerably expanded with potassium compounds 5 and 6, as well as a series of Ae coordination compounds obtained by transamination (7, 8) and organoelimination reactions (10). Interheterocycle torsion angles and N-metal bond lengths revealed the pyridylpyrrolides to be a highly flexible set of ligands. In the quest to synthesise sterically demanding benzylanilines, a facile method for the assembly of sterically congested imines (13, 14 and 15) has been developed. Yields are higher or equal to those afforded in considerably more involved literature procedures. A series of novel proligands (BzL1-4) have been synthesised and their s-block chemistry investigated, yielding lithium complex 20. An array of novel tritylamine proligands (TrL2-7) have been synthesised, and their ability to stabilise a series of highly reactive dilithium species (23-27) demonstrated. Complex 4 showed considerable activity in the catalytic heterodehydrocoupling of amine-boranes, selectively affording [Me2NBH2]2 from Me2NH•BH3 under mild conditions.